Inter-municipality translation scheme of best solid waste management practices for Dagupan City - Llamas, Rishi Arjun Nonnatus P. (2011)
This study aims to design an eclogical solid waste management (SWM) plan for the city of Dagupan, Pangasinan. The plan emphasizes on low cost source reduction strategies and non-conventional treatment and disposal alternatives that will suit the city's limited budget. The objectives were to gather baseline data on the city's solid waste, assess current SWM practices with emphasis on RA 9003 compliance and propose interventions for implementation.